Modified extracardiac Fontan with a fenestrated pericardial patch. Issue 7 (22nd May 2020) - Guariento, Alvise; Pradegan, Nicola; Castaldi, Biagio; Cattapan, Claudia; Weixler, Viktoria; Blitzer, David; Vida, Vladimiro L.
Abstract: Extracardiac Fontan is a preferred treatment strategy in many centers treating patients with single ventricle physiology, and many of these centers regularly include a fenestration between the extracardiac conduit and the common atrium. Spontaneous closure of the fenestration is a common complication of this technique and is independently associated with increased morbidity and mortality. Recently, we introduced a novel technique for fenestration of the extracardiac conduit wherein a pericardial patch is utilized at the fenestration point with excellent outcomes in the midterm fenestration patency rates, thus reducing the risk of acute post‐Fontan complications.